Enzymatic quantification of total serum bile acids as a monitoring strategy for women with intrahepatic cholestasis of pregnancy receiving ursodeoxycholic acid treatment: a cohort study. (26th September 2019) - Manna, LB; Ovadia, C; Lövgren‐Sandblom, A; Chambers, J; Begum, S; Seed, P; Walker, I; Chappell, LC; Marschall, H‐U; Williamson, C
Abstract : Objective: To evaluate enzymatic total serum bile acid quantification as a monitoring strategy for women with intrahepatic cholestasis of pregnancy (ICP) treated with ursodeoxycholic acid (UDCA). Design: Cohort. Setting: One UK university hospital. Population: 29 ICP cases treated with UDCA. Methods: Serial samples were collected prospectively throughout gestation. Total serum bile acids were measured enzymatically and individual bile acids by high‐performance liquid chromatography‐tandem mass spectrometry. Data were log‐transformed and analysed with random effects generalised least square regression. Main outcome measures: The relationship between enzymatic total bile acid measurements and individual bile acid concentrations after UDCA treatment. Results: In untreated women, cholic acid was the principal bile acid (51%) and UDCA concentrations were <0.5%, whereas UDCA constituted 60% (IQR 43–69) of serum bile acids following treatment and cholic acid fell to <20%. Changes in the total bile acid measurement reflected similar alterations in the concentrations of the pathologically elevated bile acids, e.g. a two‐fold increase in enzymatic total bile acids is accompanied by approximately a two‐fold increase in cholic acid and chenodeoxycholic acid at most UDCA doses ( P  < 0.001). Most of the effects of UDCA on cholic acid occur in the first week of treatment (60% relative reduction, P  = 0.025, 95% CI 0.2–0.9, from 10 micromol/l (4.7–17.6) to 3.5 micromol/l (1.4–7.5). Conclusion: Ursodeoxycholic acid becomes the main component of the bile acid measurement after treatment. Enzymatic total bile acid assays are good predictors of both cholic acid and chenodeoxycholic acid, the primary bile acids that are raised prior to treatment. Tweetable abstract: Ursodeoxycholic acid constitutes approximately 60% of the bile acid measurement and reduces pathological cholic acid in treated women. Tweetable abstract: Ursodeoxycholic acid constitutes approximately 60% of the bile acid measurement and reduces pathological cholic acid in treated women.